CORAK PEMIKIRAN TASAWUF KYAI SALEH DARAT SEMARANG: Kajian Atas Kitab MinhÄj Al-AtqiyÄâ€™ - Shabir, Muslich (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2017)
Kyai Saleh Darat is a scholar who wrote about 12 books using the Java language with Arabic pegon, one of them is MinhÄj al-AtqiyÄ'.Â In the book which is a translation and explanation of HidÄyat al-AdzkiyÄ' i1Ä TharÄ«q al-AuliyÄ' written by Al-Malibari, there are some personal opinions of Kyai Saleh which are able to describe his characteristic thinking of tasawuf. Generally speaking, tasawuf is divided into sunni tasawuf and falsafi tasawuf. Sunni tasawuf is tasawuf bordering and underlying the Quran and the Hadith of the Prophet as well as distancing itself from the various deviation of akidah that tend to lead to heresy and disbelief. On the other hand, falsafi tasawuf is tasawuf which is deemed to have been put into them philosophical views from outside Islam like the Indian, Greek, Persian and Christian. Supporters of this concept explain that the syari'at is not important, the more important matters is the true tauhid in accordance with the doctrine of wahdah alÂ-wujud. Observing the concept of tasawuf written in the Book of Minhaj al-Atqiya' it can be seen that tasawuf developed by Kyai Saleh is sunni tasawuf which is very stressed in syari`at practice. He is a great admirer of A1-Ghazali and the book written by him refers to the opinion of A1-Ghazali, one of the most instrumental figure in reconciling tasawuf and syariâ€™at at which therefore tasawuf is accepted by syariâ€™ah scholars—Kyai Saleh Darat merupakan seorang ulamaâ€™ yang menulis sekitar 12 kitab berbahasa Jawa dengan huruf Arab pegon yang salah satunya adalah MinhÄj al-AtqiyÄ'. Di dalam kitab yangÂ merupakan terjemah dan syarah dari HidÄyat al-AdzkiyÄ' i1Ä TharÄ«q al-AuliyÄ' karya Al-Malibari itu terdapat beberapa pendapat pribadi Kyai Saleh yang bisa menggambarkan corak pemikiran tasawufnya. Secara umum, tasawuf dibedakan menjadi dua yaitu tasawuf sunni dan tasawuf falsafi. Tasawuf sunni adalah tasawuf yang memagari dan mendasarinya dengan Al-Qur'an dan Hadits Nabi serta menjauhkan diri dari berbagai penyimpangan akidah yang cenderung membawa kepada kesesatan dan kekafiran. Di sisi lain,Â tasawuf falsafi adalah tasawuf yang dianggap telah dimasukkan ke dalamnya pandangan-pandangan filosofis dari luar Islam seperti dari India, Yunani, Persia dan Kristen. Pendukung paham ini menyatakan bahwa syari'at tidaklah penting, yang lebih penting adalah tauhid sejati yang sesuai dengan doktrin wahdah alÂ-wujud. Mencermati konsep tasawuf yang terdapat dalam Kitab Minhaj al-Atqiya'Â dapat diketahui bahwa tasawuf yang dikembangkan oleh Kyai Saleh adalah tasawuf sunni yang sangat menekankan pengamalan syari`at. Dia adalah pengagum berat A1-Ghazali dan kitab yang disusunnya banyak mengacu kepada pendapat A1-Ghazali, seorang tokoh yang paling berjasa dalam mendamaikan atau merujukkan tasawuf dan syari`at yang karenanya tasawuf diterima oleh ahli syari'ah